Encyclopedia of Information Science and Technology, Fourth Edition 2018
DOI: 10.4018/978-1-5225-2255-3.ch196
|View full text |Cite
|
Sign up to set email alerts
|

Encouraging Digital Literacy and ICT Competency in the Information Age

Abstract: This article determines the overview of digital literacy and ICT competency, the encouragement of digital literacy in the information age, and the encouragement of ICT competency in the information age. The encouragement of digital literacy and ICT competency is essential for modern organizations that seek to serve suppliers and customers, increase business performance, strengthen competitiveness, and achieve regular prosperity in the information age. Thus, it is required for modern organizations to encourage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The encouragement of digital literacy and Information Communication Technology (ICT) competency is essential for a more effective information journey, drawing upon online sources such as websites, e-journals and other e-resources. Encouraging digital literacy and ICT competency has the potential to enhance organizational performance and achieve strategic goals in the information age (Kasemsap, 2018(Kasemsap, : 2253 But what exactly is the information journey and how does it overlap with our journeys of lifelong learning? Findings by Ibekwe-SanJuan (2017) revealed six recurring themes that portray a journey of information, from its most basic manifestation as bits of data to its more complex and societal functions.…”
Section: How Modern Technologies Change the Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…The encouragement of digital literacy and Information Communication Technology (ICT) competency is essential for a more effective information journey, drawing upon online sources such as websites, e-journals and other e-resources. Encouraging digital literacy and ICT competency has the potential to enhance organizational performance and achieve strategic goals in the information age (Kasemsap, 2018(Kasemsap, : 2253 But what exactly is the information journey and how does it overlap with our journeys of lifelong learning? Findings by Ibekwe-SanJuan (2017) revealed six recurring themes that portray a journey of information, from its most basic manifestation as bits of data to its more complex and societal functions.…”
Section: How Modern Technologies Change the Experiencementioning
confidence: 99%
“…The encouragement of digital literacy and Information Communication Technology (ICT) competency is essential for a more effective information journey, drawing upon online sources such as websites, e-journals and other e-resources. Encouraging digital literacy and ICT competency has the potential to enhance organisational performance and achieve strategic goals in the information age (Kasemsap, 2018, p. 2253).…”
Section: How Modern Technologies Change the Experiencementioning
confidence: 99%
“…The fulfill the goal, education management enhancing digital competencies became the prime focus, and higher education institutions were selected as the main starting point of the development (Akarawang, Kidrakran & Nuangchalerm, 2015;Arif, Fleischer, Bogiatzis, Asada, Colombo & Zougbédé, 2018) based on the grounds that they are the scholar-producing institutions that feed workers into various industries (Inglehart, 2018;Kosaiyapattanapundit & Sangthong, 2018;Shyshkina, 2018). For that, it is justified that these institutions should be the focus and the first step for digital competency enhancement (Kasemsap, 2018;Shyshkina, 2018;Turan & Göktaş, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, many institutions have begun to develop short-term courses for the enhancement of essential competencies for undergraduate students and the implementation started with short training sessions (Freud, 2018;Hedge, 2001;Holmes, 2018;Marian Puscas, Sangineto, Culibrk & Sebe, 2015;Phanchalaem, Sujiva & Tangdhanakanond, 2016) provided to improve digital competencies deemed essential for the students. (Akarawang et al, 2015;Kasemsap, 2018;Nosenko, Shyshkina & Oleksiuk, 2018;Roşeanu & Drugaş, 2011;Shyshkina, 2018;Szabo & Marian, 2012;Trip, Vernon & McMahon, 2007) To strengthen the effort, many education institutions in Thailand came together to formulate a fundamental framework for digital competencies. Nonetheless, it was not clear, in detail, what essential components there should be for the graduate level as each higher-education institution tends to have its unique conditions and missions of existence.…”
Section: Introductionmentioning
confidence: 99%
“…The initial aspect was examined in the current study was information communication technology competency. There are various prior studies were identified that ICT competencies are significantly affect Auditing professionals [3,[10][11][12]32]. Most of the organizations using ICT enabled software to record accounting transactions.…”
Section: Discussionmentioning
confidence: 99%